The Role of Perceived Knowledge, Desirability and Feasibility in Shaping Digital Entrepreneurship Intention - Mohamed, Kartika Wati (2025)
Graduate unemployment in developing nations like Malaysia, coupled with a gap in the nation's digital innovation ecosystem, necessitates a deeper understanding of the factors driving digital entrepreneurship. This study addresses a significant gap in the literature by developing and empirically testing an integrated theoretical model to identify the antecedents of digital entrepreneurial intention (DEI) among postgraduate students. The research synthesises constructs from the Theory of Planned Behaviour (TPB), Social Learning Theory (self-efficacy) and the Entrepreneurial Intention Model to create a comprehensive framework. A cross-sectional study was conducted, gathering data from 394 Malaysian Master of Business Administration (MBA) students via an internet-mediated questionnaire. The hypothesised relationships were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The empirical findings reveal that perceived knowledge of digital entrepreneurship, personal attitude and digital entrepreneurial self-efficacy are crucial and significant antecedents of DEI. Notably, while personal attitude was a strong predictor, the traditional TPB constructs of subjective norm and perceived behavioural control were found to be non-significant, suggesting the limited influence of social pressure and general control in this context. Furthermore, the study confirms that personal attitude and digital entrepreneurial self-efficacy act as significant partial mediators, channelling the positive effect of perceived knowledge onto digital entrepreneurial intention. The findings offer critical practical implications for higher education institutions and policymakers, highlighting the need to develop curricula that emphasise ICT-based learning and hands-on digital skills to bolster student attitudes and self-efficacy. Theoretically, the study contributes a validated, integrated model that refines the TPB for the digital context and underscores the superior predictive power of domain-specific self-efficacy over general perceived control.